2006
DOI: 10.4028/www.scientific.net/kem.312.251
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Fracture Toughness of Synthetic Bone-Cement Interface

Abstract: Conventionally, the bonding strength of bone-cement interface is obtained by mechanical strength testing which tends to produce large variability between specimens and test methods. In this work, interfacial fracture toughness of synthetic bone-cement interface has been determined using sandwiched Brazilian disk specimens. Experiments were carried out under selected loading angles from 0 to 25 degrees to achieve full loading conditions from mode I to mode II. Solutions for complex stress intensity factors as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
(38 reference statements)
2
2
0
Order By: Relevance
“…Earlier study indicated that the value of K C at the bone–cement interface under Mode‐I loading was within the range of 0.5–0.8 MPa.m 1/2 (Chiang & Hung, ). Similarly, for mixed‐mode loading conditions, the value of K C was within the range of 0.1–1.6 MPa.m 1/2 , as stated in the earlier studies (Tong, ; Wang & Agrawal, ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Earlier study indicated that the value of K C at the bone–cement interface under Mode‐I loading was within the range of 0.5–0.8 MPa.m 1/2 (Chiang & Hung, ). Similarly, for mixed‐mode loading conditions, the value of K C was within the range of 0.1–1.6 MPa.m 1/2 , as stated in the earlier studies (Tong, ; Wang & Agrawal, ).…”
Section: Discussionsupporting
confidence: 83%
“…In this present study, the maximum and positive values of stress and corresponding SIF were considered (Figures ), since both the interfaces are more compliant in tension than compression (Janssen, Mann, & Verdonschot, ). The values of mixed‐mode SIF ( K I and K II ) at the bone–cement interface were obtained, and these values were within the limit of interfacial fracture toughness (K C ) as mentioned in the earlier studies (Chiang & Hung, ;Tong, ; Wang & Agrawal, ). Earlier study indicated that the value of K C at the bone–cement interface under Mode‐I loading was within the range of 0.5–0.8 MPa.m 1/2 (Chiang & Hung, ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Sandwich Brazilian disk specimens were chosen for the present study to represent the nature of loading at the bone-cement interface within the acetabular prosthetic system, which is a mixture of compression and shear [15]. Brazilian disk specimen [16] is a convenient arrangement that allows measurement of fracture toughness as a function of loading angle θ to achieve loading conditions from tensile to shear.…”
Section: Introductionmentioning
confidence: 99%